Peranan mahasiswa dalam upaya mencegah tindak pidana korupsi - Andika Wahyudi Gani; Jamil Resa (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The unique, multi-dimensional, and corrupt characteristic of corruption is one of the crimes that is difficult todismantle, because it requires steps that are carried out in extraordinary ways through its material criminal law instruments aswell as its formal crime laws. This also results in differing opinions and interpretations, both between legal differences and legaltheorists, about the limits of corruption. Various opinions given by experts and experts on corruption resolution. When viewed interms of terms, the word "corruption" comes from the Latin language, which is corruptio. IGM Nurdjana, for example, quotesfrom various sources that the Latin term corruption is "corruptie" or "curruptus", and then the word curruptio can be read fromcorrumpore (an old Latin word) from Latin which is then displayed in European languages such as English "corruption. , corrupt"French" corruption "Dutch" corruption.According to Law No. 20 of 2001 concerning Eradication of Corruption, corruption isformulated into 30 forms / types, however in general it can be grouped into seven form The unique, multi-dimensional, andcorrupt characteristic of corruption is one of the crimes that is difficult to dismantle, because it requires steps that are carried outin extraordinary ways through its material criminal law instruments as well as its formal crime laws. This also results in differingopinions and interpretations, both between legal differences and legal theorists, about the limits of corruption. Various opinionsgiven by experts and experts on corruption resolution. When viewed in terms of terms, the word "corruption" comes from theLatin language, which is corruptio. IGM Nurdjana, for example, quotes from various sources that the Latin term corruption is"corruptie" or "curruptus", and then the word curruptio can be read from corrumpore (an old Latin word) from Latin which isthen displayed in European languages such as English "corruption. , corrupt "French" corruption "Dutch" corruption.Accordingto Law No. 20 of 2001 concerning Eradication of Corruption, corruption is formulated into 30 forms / types, however in generalit can be grouped into seven forms of corruption, all of them corrupt. , and gratuity purchases.